REVITALISASI WAWASAN KEBANGSAAN MELALUI PENDIDIKAN MULTIKULTURAL - Azyumardi Azra (Institut Filsafat dan Teknologi Kreatif Ledalero, 2019)
Abstract: This article affirms the relevance of multicultural education in the endeavour to construct nationalistic ideals that covers four pillars: Pancasila, the Unitary State of Indonesia, the 1945 Constitution, and Unity in Diversity. Even though the conception of nation-state based on Pancasila has become the national consensus since 1945, it must be admitted that lately nationalistic ideals have increasingly been threatened by primordialistic religious practices. The formation of a multicultural society in Indonesia that is based on nationalistic ideals must be conducted systematically, structurally, integrally, and sustainably. In that context the approach of multicultural education is very relevant. Specifically, the concept of multicultural education includes acknowledgement of individual cultural differences of minority groups. The concept of multicultural education contains aspirations as well as efforts to respect the dignity of each person.Keywords: nationalistic ideas, Pancasila, national identity, multicultural education, diversity, multiculturalism, civil society